Insights from genesis stories of Tamu (Gurung) of Nepal and Naxi of Yunnan (China) - Gurung, Tek Bahadur (Journal of Nepalese Studies, 2024)
The existence of myths or folktales about origins among various communities and societies are subjects of academic discourse. These stories are observable among people, as they offer believers explanation that fulfill their cultural and spiritual needs. Academically, they provide valuable insights for comparative analysis. This article examines the origin stories prevalent among the Tamu (the Gurungs) of Nepal and the Naxi ethnic minority in China’s Yunnan province. The Tamu story postulates their origin can be traced back to the mythical Khe Ku (nine paternal ancestors) and Mhā Ngi (seven maternal ancestors). Similarly, the Naxi story features nine paternal and seven maternal progenitors despite the fact that these communities being located in different countries and speaking distinct languages. While further studies are needed, the genetic affinity between the Naxi community and the Tamu community (and other indigenous nationalities of Nepal) suggests that the inhabitants of this region embody contemporary manifestations of a shared prehistoric lineage or horde.